2021
DOI: 10.1038/s41586-021-03829-0
|View full text |Cite
|
Sign up to set email alerts
|

The EDS1–PAD4–ADR1 node mediates Arabidopsis pattern-triggered immunity

Abstract: Plants deploy cell-surface and intracellular leucine rich-repeat domain (LRR) immune receptors to detect pathogens 1 . LRR receptor kinases and LRR receptor proteins at the plasma membrane recognize microorganism-derived molecules to elicit pattern-triggered immunity (PTI), whereas nucleotide-binding LRR proteins detect microbial effectors inside cells to confer effector-triggered immunity (ETI). Although PTI and ETI are initiated in different host cell compartments, they rely on the transcriptional activation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
283
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 295 publications
(289 citation statements)
references
References 58 publications
6
283
0
Order By: Relevance
“…NLRs perceive pathogen secreted proteins known as effectors and induce robust immune responses that generally include hypersensitive cell death (Jones et al, 2016;Kourelis and van der Hoorn, 2018;Saur et al, 2021). NLR-mediated immunity (also known as effector-triggered immunity) can be effective in restricting pathogen infection at invasion sites, and NLRs have also been recently shown to be involved in PRR-mediated signalling (Ngou et al, 2021a;Pruitt et al, 2021;Tian et al, 2021;Kourelis et al, 2021b). However, NLR-mediated immunity comes at a cost for plants.…”
Section: Introductionmentioning
confidence: 99%
“…NLRs perceive pathogen secreted proteins known as effectors and induce robust immune responses that generally include hypersensitive cell death (Jones et al, 2016;Kourelis and van der Hoorn, 2018;Saur et al, 2021). NLR-mediated immunity (also known as effector-triggered immunity) can be effective in restricting pathogen infection at invasion sites, and NLRs have also been recently shown to be involved in PRR-mediated signalling (Ngou et al, 2021a;Pruitt et al, 2021;Tian et al, 2021;Kourelis et al, 2021b). However, NLR-mediated immunity comes at a cost for plants.…”
Section: Introductionmentioning
confidence: 99%
“…The PTI/ETI distinction as originally proposed has blurred with the discovery and characterization of more receptor/ligand pairs and their downstream partners, which have revealed the overlap between resistance mechanisms ( 20 , 52 , 93 ). Similarly, as more microbial factors are identified that do not neatly fit into the PAMP vs. effector dichotomy, such classifications may lose relevance ( 91 , 94 97 ).…”
Section: Terminologymentioning
confidence: 99%
“…SOBIR1 interacts with RLP23 to facilitate immune response to Pst ( 142 ). The RLP23/SOBIR1 complex, which also requires BAK1 coreceptor for function, is particularly interesting because the output requires proteins that were previously shown to be essential to immunity mediated by the NBS-LRR intracellular class of receptors ( 94 ). In addition to Arabidopsis RLP23, SOBIR is essential for the function of other RLPs, such as Cf-4 in tomato, indicating its broad involvement in RLP-mediated immunity as a coreceptor ( 94 , 141 ).…”
Section: Tyrosine Sulfation Mediates Extracellular Protein–protein In...mentioning
confidence: 99%
“…PTI can enhance resistance from PTI. The PTI and ETI comprising the two-tiered plant immune system that monitors threats from pathogens are not separable and collaboratively contribute to the reciprocal enhancement of plant immunity ( Ngou et al, 2021 ; Pruitt et al, 2021 ; Yuan et al, 2021 ; Tian et al, 2021 ). HR as one canonical type of PCD in plants is beneficial to the host likely by eliminating the intracellular niche for proliferation of certain pathogens.…”
Section: Introductionmentioning
confidence: 99%
“…Reprogramming of immune genes enforces resistance. The ADR1-EDS1-PAD4 module can be polymerized with the complex formed by LRR-RP-SOBIR1 and PBL31 of the RLCK family to form a supramolecular complex, which not only binds the inner leaflet of the plasma membrane to mediate the response of PTI but ADR1 is contributive to TNL-directed resistance signaling involved in reprogrammed transcription of pathogenesis-responsive genes ( Pruitt et al, 2021 ) ( Figure 3C ).…”
Section: Introductionmentioning
confidence: 99%